Aspects of the measurement of the acoustic transfer function in a cavitation tunnel. (June 2019) - Tani, Giorgio; Viviani, Michele; Ferrando, Marco; Armelloni, Enrico
Abstract: Model scale experiments represent one of the most effective, and probably the most commonly used, approaches for the study of cavitating propeller noise. Despite this, the acquirement of consistent data of propeller noise from tests in model scale facilities is still a challenging task. Data collected with such an approach are usually affected by several scale effects and facility related issues which make such experiments still very complex. Among others, the effect of the facility itself as acoustical surrounding must be carefully addressed in order to properly estimate propeller source levels in ideal free field conditions. This is currently carried out, when possible, by measuring facility transfer functions and applying such functions as a correction to measured noise spectra. The development of robust procedures for the measurement of these transfer functions is thus very important. In the present work, this problem is addressed by discussing in details techniques, merits and possible problems related to this topic.